Immunotherapeutic approaches in the treatment of herpetic infections - Skrotska, Oksana; Lych (Tkachenko), Inna; Solominchuk, V.; Zholobak, Nadezhda (My University, 2012)
The possible consequences of human infecting by Herpesviridae are shown. The basic classes of preparations used in Ukraine for the immunotherapy of Herpesviridae infections, in particular interferons, inductors of interferons and immunomodulators are described. The comparative description these preparations and their advantages and disadvantages are presented.
Keywords: herpesviridae; interferons; inductors of interferons; immunomodulators; герпес; інтерферони; індуктори інтерферонів; імуномодулятори; интерфероны; индукторы интерферонов; иммуномодуляторы; кафедра біотехнології і мікробіології